THE USE OF FREIES ERMESSEN (DISCRETION) IN TH ACTIVITY OF CENTRAL GOVERNMENT AND LOCAL GOVERNMENT - Aldi Frinaldi (Muhammadiyah Law Review Journal, 2017)
Nowadays Indonesia has a tendency to apply the legal sistem administratively, which dominate in every activities include public administration must be on rules written. If there are conditions in making of legislations that runs low, or their conditions had not been anticipated in certain condition. Beside that, there is the dynamic development of social life runs rapidly that requires immediate treatment by government or local government. In this circumstance, it requires the autonomy of the government to act in dealing with issues that happened. The use of freies ermessen can be shown to emerge certain innovation from the bureaucracy reformation for public interest. The form of this freies ermessen can be shown in some forms such as circular letter, guidance, and announcement, abstract and general letter of decision as well as in a form f regulation which is called pseude-wet giving.